The Effect of Ankle Weight Training Method on Free Kick Results in Soccer Games in Extracurricular Students at Al-Amanah Al-Islami Ridan Permai Islamic Boarding School - Jufrianis Jufrianis; Ikhsan Afandi (Siber Nusantara Review, 2026)
This study aims to determine the effect of the ankle weight training method on the results of free kicks in soccer games for extracurricular students at the Al-Amanah Al-Islami Ridan Permai Islamic Boarding School. The method used is an experiment with a One Group Pretest and Posttest Design, involving a population of 30 people and a sample of 22 people determined by purposive sampling technique. The instrument used is a kicking ability test to measure free kick ability. Data were analyzed using the Kolmogorov Smirnov normality test, followed by One Way ANOVA analysis and the Paired Sample T test. The results of the analysis based on statistical output are known asymp. Sig. (2-tailed) is 0.001. Because the value of 0.001 is smaller than 0.05. It can be concluded that